Genocide on Trial: Case Note and Extracts of "Circuito Camps" Judgment - Riveiro, María Belén (2013)
Since 2006, several Argentine courts have tried the crimes committed during the 1976 dictatorship. While in most countries these crimes are usually tried by International Tribunals or by Mixed Jurisdiction Tribunals, in Argentina national courts have been responsible of this task. We will analyze a judgment that considers that these crimes entail the commission of the crime of Genocide.